2004
DOI: 10.3348/kjr.2004.5.3.178
|View full text |Cite
|
Sign up to set email alerts
|

US Features of Transient Small Bowel Intussusception in Pediatric Patients

Abstract: ObjectiveTo describe the sonographic (US) and clinical features of spontaneously reduced small bowel intussusception, and to discuss the management options for small bowel intussusception based on US findings with clinical correlation.Materials and MethodsDuring a five years of period, 34 small bowel intussusceptions were diagnosed on US in 32 infants and children. The clinical presentations and imaging findings of the patients were reviewed.ResultsThe clinical presentations included abdominal pain or irritabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
56
0
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 19 publications
5
56
0
5
Order By: Relevance
“…The widest intussusception in our series had a diameter of 2.5 cm. Our findings agree with the results (mean diameter 1.5 cm) of Kim [10]. Strouse et al [7] found a mean short-axis diameter of 2.1 cm (range, 1.5-3.0 cm) for small bowel intussusceptions identified on CT.…”
Section: Discussionsupporting
confidence: 92%
“…The widest intussusception in our series had a diameter of 2.5 cm. Our findings agree with the results (mean diameter 1.5 cm) of Kim [10]. Strouse et al [7] found a mean short-axis diameter of 2.1 cm (range, 1.5-3.0 cm) for small bowel intussusceptions identified on CT.…”
Section: Discussionsupporting
confidence: 92%
“…More than 90% of cases of intussusception that occur in pediatric patients are of an ileo-colic, ileo-cecal, or ileoileo-colic type. 1 Distinctly, more than 50% of adult intussusceptions are small bowel intussusceptions (SBI), and they are secondary to an underlying disease (eg, neoplastic tumors). 2 Transient SBI in children is accepted to be infrequent in the medical literature.…”
Section: Discussionmentioning
confidence: 99%
“…13,16 Absence of color flow in Doppler suggests compromise of the mesenteric vasculature, indicating a potentially difficult reduction and a lower reduction success rate. 1,17,18 Characteristic US findings of the transient small bowel "ileal-ileal" intussusception include small size of the doughnut ring (2-3 cm), no recognizable lead point, short segment length of less than 3.5 cm, normal vascularity on color Doppler US, and preserved wall motion. 1,4,13,16,17,[19][20][21] Due to the availability of US imaging in most emergency departments, small bowel intussusceptions may be readily identified and characterized by these recommended criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Since an unreduced intussusception can potentially cause bowel obstruction and mesenteric vascular compromise leading to bowel ischemia/necrosis, early diagnosis and treatment of this disease are very important (Fig. 1) [1][2][3]. The pathogenesis of intussusception is in approximately 90 % of cases idiopathic and is assumed to be secondary to uncoordinated peristalsis of the gut or to lymphoid hyperplasia, which may be due to a recent GI infection [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The ''classic'' clinical triad has been described as consisting of (a) acute colicky abdominal pain, (b) ''currant jelly'' or frankly bloody stools, and (c) either a palpable abdominal mass or vomiting. Many children do not present the complete triad of symptoms and in some cases intussusception may be transient with spontaneously reduction [3,7,13,14].…”
Section: Introductionmentioning
confidence: 99%